PENANAMAN NILAI KARAKTER TANGGUH DAN PEDULI MELALUI PROGRAM SOCIAL SKILL DI SMA AL HIKMAH SURABAYA - Musyafa, Musyafa (Universitas Negeri Semarang, 2017)
This study aims to determine the value Planting of strong character and care through social skills program in SMA Al Hikmah Surabaya. The research was conducted on students who take the program of social skills class XI in the school year 2014-2015 in the village Parerejo, Purwodadi, Pasuruan. Implementation of the research in May-June, 2015.This study used a qualitative method with a grounded theory approach. Research using instruments: (1) direct observation (2) field notes (3) interviews and (6) documentation. This study identified two themes in his research consisted of planting the value of strong character through a social skills program, and implantation on the character concerned with social skills program. Two themes are based on research goals predetermined and interconnected to form a theory of value investment of strong character and care. In this study, students follow a program of activities that instill values of toughness and concern to the students through several activities, namely home stay program residents, social service and leadership. From the research there is a positive response from the students to the values of strong character, especially in terms of attitude: to make an effort, enthusiasm, patience, perseverance, and a high work ethic. Similarly, there is a positive response to the values of the characters to care, especially in terms of attitude: helpful, respectful and civil, discipline, empathy, and unpretentious.